Ictiólogos de la Argentina : María Luisa Fuster de Plaza - López, Hugo Luis (2009)
Fil: López, Hugo Luis. División Zoología Vertebrados; Facultad de Ciencias Naturales y Museo; Universidad Nacional de La Plata